Persistent generation of hydroxyl radicals in Tris–Co(ii) complex–H2O2 systems for long-lasting multicolored chemical lights. Issue 5 (19th December 2018) - Li, Zhe; Wang, Lianying; Yuan, Zhiqin; Lu, Chao
Abstract : Aqueous luminol tablet–Tris–Co(ii )–PVP–H2 O2 chemical light systems through the continuous generation of ˙OH and sustained luminol and H2 O2 release are presented. Abstract : Luminol tablet–Tris–Co(ii ) complex–PVP–H2 O2 systems exhibit 13 hours of intensive and stable chemiluminescence (CL) due to the continuous generation of ˙OH and sustained-release. Multicolored chemical lights were prepared through CL resonance energy transfer. This work presents a new method for the fabrication of bright chemical lights in aqueous solution for emergencies.